Impact Of Communication Technology On Leadership Skills Of Managers In The IT Sector - Ramaswamy, Parameswaran (Digital Repository of Theses, 2025)
The digital transformation of organizations has reshaped leadership in fundamental ways, particularly in the IT sector where distributed teams, globalized operations, and rapid project cycles make reliance on communication technologies unavoidable. This study investigated how communication technologies shape leadership skills among IT managers, focusing on four widely used tools: email, instant messaging, video conferencing, and dashboards. The study pursued three objectives: (1) to examine the adoption patterns of these tools, (2) to evaluate their perceived impact on core leadership skills—communication effectiveness, decision-making, motivation, trust-building, and adaptability—and (3) to statistically test the relationships between tool adoption and leadership effectiveness. The findings revealed that technologies exert differentiated impacts rather than universally enhancing leadership. Email supported accountability, instant messaging boosted motivation, video conferencing fostered trust and decision-making, and dashboards strengthened adaptability. These results confirm but also extend media richness and social presence theories by demonstrating that lean tools, such as dashboards, can still enable leadership when aligned with structural needs. A second finding emphasized that Leaders who combined platforms strategically reported higher effectiveness and adaptability than those who relied too heavily on a single medium. This reframes leadership as a practice of communication system design, where success lies in balancing speed, inclusivity, and oversight across tools. The study also found that leadership outcomes are moderated by demographic and contextual factors such as age, gender, experience, and team size, extending situational leadership theory into digital contexts. Furthermore, the results highlighted relational paradoxes: technologies that enhanced speed and transparency also risked fatigue, depersonalization, and overload. These findings yield several contributions. Theoretically, the study refines media theories, extends situational leadership into digital domains, identifies paradoxical dynamics, and positions adaptability at the core of leadership theory. Practically, it provides actionable guidance for leaders, for organizations, and for policy makers. Methodologically, it demonstrates the value of linking specific tools to leadership skills, combining multiple forms of analysis, and foregrounding India’s IT sector as a globally significant research context. In conclusion, this thesis shows that communication technologies are not neutral backdrops but active forces that reshape leadership practice. Effective leadership in the IT industry requires the ability to orchestrate technologies, adapt to situational demands, and manage the paradoxes of digitally mediated work.